Psychological Treatment in Early Adult Women with Major Depressive Disorder - Mardhiyah, Fairuz Ghina; Surjaningrum, Endang R. (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Major Depressive Disorder (MDD) is a form of an episode of mood disorder (mood) where feelings of pressure (depression) more dominate individual behavior. The individual who experiences this disorder will cause symptoms from cognitive, emotional, and motor behavior to motivational aspects. This paper presents a case of depression and management carried out on Client RAH a female and 23-year-old. Giving rise to a depressive disorder due to her inability to express the emotions she feels, feeling worthless, and several symptoms significantly affected her functioning capacity of the individual until she attempted suicide. The series of assessments carried out on RAH Clients aims to explore further related to their problems. The process of establishing diagnoses through a series of evaluations, namely clinical interviews, observations, Graphic Tests (BAUM, DAP, HTP), DASS (Depression Anxiety Stress Scale), SSCT (Sacks Sentence Completion Test), BDI (Beck Depression Inventory), and TAT (The Thematic Apperception Test). The results showed that the RAH Client met the criteria for diagnosing Major Depressive Disorder (MDD) with a moderate level based on the DSM-5 criteria. The treatment action that can be done based on the results of assessment and diagnosis is to use the Free Association technique, which aims to reduce the act of hurting herself and improve her decision-making ability.Major Depressive Disorder (MDD) merupakan salah satu bentuk episode gangguan mood (suasana hati) dimana secara jelas perilaku individu lebih didominasi dengan perasaan tertekan (depresi). Individu yang mengalami gangguan ini akan memunculkan gejala dari aspek kognitif, emosional, perilaku motorik, hingga motivasi. Naskah ini menyajikan satu kasus depresi dan pengelolaan yang dilakukan terhadap Klien RAH berjenis kelamin perempuan dan berusia 23 tahun memunculkan gangguan depresi akibat kurang mampunya untuk mengeluarkan emosi yang dia rasakan, merasa tidak berharga, dan beberapa gejala yang signifikan mempengaruhi kapasitas fungsi individu hingga adanya usaha percobaan bunuh diri. Rangkaian asesmen yang dilakukan kepada Klien RAH bertujuan untuk menggali lebih jauh terkait permasalahan yang dihadapi olehnya. Proses penegakan diagnosa melalui serangkaian asesmen yaitu wawancara klinis, observasi, Tes Grafis (BAUM, DAP, HTP), DASS (Depression Anxiety Stress Scale), SSCT (Sacks Sentence Completion Test), BDI (Beck Depression Inventory), dan TAT (The Thematic Apperception Test). Hasil menunjukan bahwa Klien RAH memenuhi kriteria diagnosa Major Depressive Disorder (MDD) dengan tingkatan moderate berdasarkan kriteria DSM-5. Tindakan penanganan yang dapat dilakukan berdasarkan hasil asesmen dan diagnosa adalah dengan menggunakan teknik Free Association yang bertujuan untuk mengurangi tindakan menyakiti dirinya dan meningkatkan kemampuan dalam pengambilan keputusan.